INTERACTING WITH THE QUR’AN IN PANDEMIC TIMES: THE STUDY OF LIVING THE QUR’AN AT PONDOK PESANTREN - Faizah, Thoriqotul (Universitas Nurul Jadid, 2021)
This study aims to explore the interaction of students at the Pondok Pesantren Nurul Jadid Paiton, Probolinggo, East Java, with the Qur’an, both online and offline, to reveal changes in methods during the pandemic. With the field approach and reception theory, two forms of student interaction with the Qur’an were found, namely aspects of memorization and understanding; aspects of memorization that are carried out offline or online the pandemic as well as aspects of understanding that students choose through youtube instead of majelis ta’lim as an alternative in increasing knowledge in the field of the Qur’an. This article examines the form of interaction with the Qur’an through programmed activities with a pesantren background. In this article, the researcher describes why or what is wrong with the study of the Qur’an during the pandemic? Because during the pandemic, the learning method underwent several changes considering the impact of the pandemic spread that occurred since the end of 2019 certainly had an overall effect, including the education sector, at the pondok pesantren. This study uses a qualitative approach that is a case study; the authors try to analyze and describe how the students of the Pondok Pesantren Nurul Jadid interact with the Qur’an through the memorization and understanding methods applied by the students, especially during the pandemic.